Morpho-Anatomical, Ex-situ Conservation and Haemolytic Activity of Pentaphragma grandiflorum Kurz.: Morpho-anatomy, Ex-situ Conservation and Haemolytic Activity of Pentaphragma grandiflorum Kurz - Amoroso, Victor; M. Maghanoy, Lalaine Grace; Aser, Cristine Mea (Journal of Tropical Life Science, 2023)
Pentaphragma grandiflorum Kurz. is one of the five (5) species of Pentaphragma that is found in the Philippines. It is an edible flowering plant consumed as a vegetables and utilized for its medicinal value by the locals. It is categorized as one of the Other Threatened Species with a high economic value. Despite the many uses of P. grandiflorum, there is still inadequate information on its morpho-anatomical characteristics conservation and lack of scientific evidence to support the claim of its safe utilization by the locals. The collected wildlings of the P. grandiflorum were nurtured and monitored in the canopy greenhouse of Central Mindanao University, Philippines. The safe utilization of the leaf extract of P. grandiflorum was assessed through a haemolytic assay. The following are the morpho-anatomical features described in this study: fleshy erect shrub with primary and aerial roots; stem puberulous at a young stage and glabrous upon maturity with dictyostele type of stele; petiole fleshy, puberulous, dissected vascular bundle with dictyostele arrangement; leaf finely puberulous adaxial and glabrous abaxial, dictyostele arrangement, midrib amphibrical arrangement, with tri- to tetracytic stomates; inflorescence arises singly in axil, bisexual, elongated, with yellow and/or purple corolla. Fifty-three out of 130 wildlings survived and abundantly produced bisexual flowers in the succeeding months. The 1 mg/mL concentration of ethanolic and methanolic leaf extracts of P. grandiflorum were found to have an average haemolysis percentage of 0.32 ± 6.78 and 0.45 ± 0.65, respectively. The result of the haemolysis assay revealed that the ethanolic and methanolic leaf extract of P. grandiflorum is safe to utilize and do not pose any toxic effects to humans.